1989
DOI: 10.1111/j.1348-0421.1989.tb00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Herpes Simplex Virus in Yogyakarta, Indonesia

Abstract: Sera from 487 individuals in Yogyakarta, Indonesia, were tested for antibodies to herpes simplex virus (HSV) by a passive hemagglutination method. Age-specific incidence rates for antibodies to HSV were calculated. For sera from persons other than prostitutes, in the age group from 10 to 19, the positive rate was 48% but in the age group higher than 20, it was more than 87% . Fifty of 59 pregnant women (85%) were positive. The positive rate and the distribution of antibody levels in prostitutes were higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
1991
1991

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The incidence of antibodies to HSV-l increases with age but varies considerably with socioeconomic conditions (3,5,7,9,10) . Our group has reported a difference in age distribution of antibodies to HSV-l among the sera from Fukuoka, Manila, Busan, and Indonesia (1,4) . Since no seroepidemiological studies on HSV-l infection in China have been reported, sera from 158 individuals in Yanji, Jilin, an area in northeastern China, were tested for antibodies to HSV-l by the passive hemagglutination (PHA) method.…”
mentioning
confidence: 99%
“…The incidence of antibodies to HSV-l increases with age but varies considerably with socioeconomic conditions (3,5,7,9,10) . Our group has reported a difference in age distribution of antibodies to HSV-l among the sera from Fukuoka, Manila, Busan, and Indonesia (1,4) . Since no seroepidemiological studies on HSV-l infection in China have been reported, sera from 158 individuals in Yanji, Jilin, an area in northeastern China, were tested for antibodies to HSV-l by the passive hemagglutination (PHA) method.…”
mentioning
confidence: 99%